2021
DOI: 10.3390/foods10061299
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Characterization of Water-Soluble Constituents in Olive-Derived By-Products

Abstract: Olive trees constitute one of the largest agroindustries in the Mediterranean area, and their cultivation generates a diverse pool of biomass by-products such as olive tree pruning (OTP), olive leaves (OL), olive stone (OS), and extracted olive pomace (EOP). These lignocellulosic materials have varying compositions and potential utilization strategies within a biorefinery context. The aim of this work was to carry out an integral analysis of the aqueous extractives fraction of these biomasses. Several analytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…Regarding mannitol, the amount extracted from EOP by MAWE under optimized conditions, 46.7 mg/g EOP ( Table 3 ), was higher than that obtained with water as a solvent using a Soxhlet extractor overnight (40 mg/g EOP) [ 11 ] and in a bath at 85 °C for 90 min (45 mg/g EOP) [ 7 ] or at 100 °C for 30 min (39 mg/g EOP) [ 25 ]. In addition, it is worth noting that these amounts of mannitol extracted from EOP are in the range of the values obtained from olive leaves, which are considered a rich source of mannitol [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding mannitol, the amount extracted from EOP by MAWE under optimized conditions, 46.7 mg/g EOP ( Table 3 ), was higher than that obtained with water as a solvent using a Soxhlet extractor overnight (40 mg/g EOP) [ 11 ] and in a bath at 85 °C for 90 min (45 mg/g EOP) [ 7 ] or at 100 °C for 30 min (39 mg/g EOP) [ 25 ]. In addition, it is worth noting that these amounts of mannitol extracted from EOP are in the range of the values obtained from olive leaves, which are considered a rich source of mannitol [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that it is easier to extract the proteinaceous material from EOP than from olive leaves or olive tree pruning using hot water [ 11 ]. This can explain the partial solubilization of the EOP protein observed in this work.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, one of the papers of this SI [21] reports on the analytical characterization of four diverse pools of biomass by-products such as OTP, OL, OS and extracted olive pomace (EOP) to highlight their potential recovery of the water-extractable fraction within a biorefinery context. The final aim was to assess the occurrence of high-value-added compounds as carbohydrates, proteins, alditols and to ascertain a comparison between the four different olive biomasses of their structural composition and quantity in the water extractives.…”
mentioning
confidence: 99%